Chronic ethanol vapor exposure potentiates cardiovascular responses to acute stress in male but not in female rats - Bianchi, Paula C. [UNESP]; Gomes-de-Souza, Lucas [UNESP]; Costa-Ferreira, Willian [UNESP]; Palombo, Paola [UNESP]; Carneiro de Oliveira, Paulo E.; Engi, Sheila A.; Leão, Rodrigo M.; Planeta, Cleopatra S. [UNESP]; Crestani, Carlos C. [UNESP]; Cruz, Fabio C. (Springer Nature, 2021)
BACKGROUND: Ethanol use is related to a wide variety of negative health outcomes, including cardiovascular diseases. Stress is also involved in numerous pathologies, such as cardiovascular diseases and psychiatric disorders. Sexual dimorphism is an important factor affecting cardiovascular response and has been proposed as a potential risk factor for sex-specific health problems in humans. Here, we evaluated the effect of prolonged ethanol vapor inhalation on arterial pressure, heart rate, and tail skin temperature responses to acute restraint stress, investigating differences between male and female rats. METHODS: We exposed male and female Long-Evans rats to ethanol vapor for 14 h, followed by ethanol withdrawal for 10 h, for 30 consecutive days, or to room air (control groups). The animals underwent surgical implantation of a cannula into the femoral artery for assessment of arterial pressure and heart rate values. The tail skin temperature was measured as an indirect measurement of sympathetic vasomotor response. RESULTS: Chronic ethanol vapor inhalation reduced basal heart rate in both female and male rats. Sex-related difference was observed in the decrease of tail cutaneous temperature evoked by stress, but not in the pressor and tachycardiac responses. Furthermore, prolonged ethanol inhalation enhanced the blood pressure and heart rate increase caused by acute restraint stress in male, but not in female rats. However, no effect of chronic ethanol vapor was observed in the tail cutaneous temperature response to restraint in either sex. CONCLUSION: Chronic ethanol vapor exposure increased the cardiovascular reactivity to stress in male, but not in female rats.
Keywords: Alcohol; Blood pressure; Heart rate; Restraint stress; Sex